A new species of Eutropis (Squamata: Scincidae) from Sri Lanka - Das, I.; De Silva, A.; Austin, C.C (Zootaxa, 2008)
A new species of lygosomine scincid lizard of the genus Eutropis is described from the dry and intermediate zones of the lowlands (0–190 m asl) of Sri Lanka. Eutropis tammanna sp. nov. is compared with congeners from Sri Lanka and those from southern Peninsular India, and is diagnosable by molecular data and by the following combination of morphological characters: body size small, up to 52.3 mm; transparent window-like disk absent on lower eyelids; prefrontals in broad contact; a single pair of nuchals; postnasal absent; ear opening larger than adjacent scales; dorsal scales with 6–7 keels; midbody scale rows 28–29; paravertebral scale rows 37–40; ventral scales 41–48; lamellae under fourth toe 15–16; dark labial bars present in both sexes, which are more distinct in males; dark postocular stripe absent; males brown on dorsum, with dark flanks speckled with cream; females similar to males, the pattern less contrasting, lacking paired series of black markings, pale vertebral stripes or dark longitudinal stripes on dorsum. In addition, the rostral, labials, and gular region of presumed breeding males are bright flame scarlet.